Answer:
<u><em></em></u>
- <u><em>Yes, it is reasonable to expect that more than one subject will experience headaches</em></u>
Explanation:
Notice that where it says "assume that 55 subjects are randomly selected ..." there is a typo. The correct statement is "assume that 5 subjects are randomly selected ..."
You are given the table with the probability distribution, assuming, correctly, the binomial distribution with n = 5 and p = 0.732.
- p = 0.732 is the probability of success (an individual experiences headaches).
- n = 5 is the number of trials (number of subjects in the sample).
The meaning of the table of the distribution probability is:
The probability that 0 subjects experience headaches is 0.0014; the probability that 1 subject experience headaches is 0.0189, and so on.
To answer whether it <em>is reasonable to expect that more than one subject will experience headaches</em>, you must find the probability that:
- X = 2 or X = 3 or X = 4 or X = 5
That is:
- P(X = 2) + P(X = 3) + P(X = 4) + P(X = 5).
That is also the complement of P(X = 0) or P(X = 1)
From the table:
- P(X = 0) = 0.0014
- P(X = 1) = 0.0189
Hence:
- 1 - P(X = 0) - P(X = 1) = 1 - 0.0014 - 0.0189 = 0.9797
That is very close to 1; thus, it is highly likely that more than 1 subject will experience headaches.
In conclusion, <em>yes, it is reasonable to expect that more than one subject will experience headaches</em>
There are 60 seconds in a minute.
There are 60 minutes in an hour.
This means that there'd be 600 minutes in 10 hours.
And if there are 60 seconds in a minute, there are 600 x 60 seconds in 600 minutes.
600 x 60 = 600 x 10 x 6 = 6000 x 6 = 36000
So we know that there are 36000 seconds in 10 hours.
7-4=3
........................
Answer:wanna hang
Step-by-step explanation:
<span>A system of equations has infinitely many solutions when the two
lines representing the equations coincide. i.e. the two equations are
the same or a multiple of each other.
2y - 4x = 6
2y = 4x + 6
2y = 2(2x + 3)
y = 2x + 3
-y = -(2x + 3)
-y = -2x - 3
Hence the other equation is -y = -2x - 3</span>